2015
DOI: 10.1152/ajpcell.00296.2014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NHE8 expression impairs ocular surface function in mice

Abstract: Sodium/hydrogen exchanger (NHE) 8 is expressed at the apical membrane of the epithelial cells and plays important roles in neutral sodium absorption in the gastrointestinal tract and the kidney. It also has an important role in epithelial mucosal protection in the gastric gland and the intestine. Although NHE8 has broad tissue distribution, the precise location and the physiological role of NHE8 in the eye remain unknown. In the present study, we successfully detected the expression of NHE8 in the ocular surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…13,15 Furthermore, it has been reported recently that the gene is expressed in the epithelial cells of the conjunctiva, cornea, and lacrimal glands and may have a role in the protection of these ocular epithelia. 16 The male mutants also are sterile.…”
mentioning
confidence: 99%
“…13,15 Furthermore, it has been reported recently that the gene is expressed in the epithelial cells of the conjunctiva, cornea, and lacrimal glands and may have a role in the protection of these ocular epithelia. 16 The male mutants also are sterile.…”
mentioning
confidence: 99%
“…Mice with targeted ablation of the Slc9a8 gene showed that gastric expression of NHE8 was critical for the maintenance of bicarbonate secretion by the Cl − /HCO 3 − exchanger downregulated-in-adenoma (DRA; Slc26a3 ), and that compared with their wild-type littermates, Nhe8 -deficient mice had a higher incidence of gastric ulcer formation (315). Although the mechanism responsible for downregulation of DRA expression remains unknown, it appears to be a phenomenon consistent across organs as it was also described in the colon (321), conjunctiva, cornea, and the lacrimal glands (322). …”
Section: Na+/h+ Exchange In Gastric Physiologymentioning
confidence: 60%
“…Compared with their wild-type littermates, mice lacking NHE8 had a higher incidence of gastric ulcer formation 32 . Although the mechanism responsible for DRA down-regulation is not yet clear, it appears to be a phenomenon consistent across organs because it was described also in the colon, 41 conjunctiva, the cornea, and the lacrimal glands 42 …”
Section: Na+/h+ Exchange In Esophageal and Gastric Pathologymentioning
confidence: 99%